Importance of surveillance of tularemia natural foci in the known endemic area of Central Europe, 1991-1997 - Gurycová, D; Výrosteková, V; Khanakah, G; Kocianová, E; Stanek, G (Wiener klinische Wochenschrift, 2001)
INTRODUCTION AND PURPOSE: Marked activation of natural foci of tularemia in the known endemic area of Central Europe, comprising the borderland of Slovakia, Austria and the Czech Republic, led to an epidemic outbreak in western Slovakia and an increase in the number of human tularemia cases in the adjoining regions of northeastern Austria and southern Moravia from 1995 to 1997. The aim of this paper was to present the results of a longitudinal study on the prevalence of infection with Francisella tularensis in small mammals and ticks in six localities of western Slovakia and northeastern Austria from 1991 to 1997, and to draw attention to the importance of systematic surveillance of natural foci for epidemiologic prognoses and for taking preventive measures. METHODS: In Slovakia, three localities of the Záhorie lowland were monitored for 3 to 6 years (1991 to 1996) for the presence of F. tularensis in small terrestrial mammals. In Austria, small mammals and ticks from three localities were investigated for 1 to 3 years (1994 to 1997). Spleens of live-trapped animals (at 1- to 2-month intervals) and ticks collected by flagging (in 6- to 8-week intervals) were examined by inoculation of pools into white mice, or individually by cultivation. RESULTS: In four localities under investigation (three localities in western Slovakia and one in Austria), a nearly simultaneous flare-up of tularemia epizootics was recorded in the autumn of 1994. The highest mean prevalence of infection in small mammals was 3.9% in the last quarter of the year, which along with isolations of F. tularensis from Dermacentor reticulatus ticks collected from vegetation in the locality of Austria (1.3% positivity), indicated the high epizootic activity of foci. F. tularensis was isolated from five rodent species--Apodemus flavicollis, A. sylvaticus, Clethrionomys glareolus, Microtus arvalis and Sorex araneus. From 1995 to 1996, the persistent activity of the focus was repeatedly confirmed by isolations of F. tularensis from D. reticulatus ticks. In 1995 a natural focus of tularemia was detected in a further locality of Austria, where the agent was isolated from D. reticulatus. The increased epizootic activity of foci in the endemic region of Central Europe indicated a higher risk of acquiring tularemia for humans and was, in fact, followed by an epidemic outbreak in western Slovakia as well as by a large number of cases in Austria and the Czech Republic. CONCLUSION: Our findings clearly demonstrate that long-term surveillance of natural foci in endemic regions provides useful information on the activation of tularemia foci before the onset of epidemic outbreaks, thus permitting timely epidemiologic prognoses and the institution of preventive measures.
Keywords: Zoonoses; Tick-Borne Diseases; hlodavci; Slovakia; longitudinální studie; Slovenská republika; zdroje nemoci; Rakousko; tularemie; Rodentia; Česká republika; Population Surveillance; zoonózy; incidence; nemoci přenášené klíšťaty; Czech Republic; Animals; lidé; Humans; zvířata; Tularemia; epidemický výskyt choroby; Disease Reservoirs; Austria; surveillance populace; Dermacentor; Longitudinal Studies; Incidence; Disease Outbreaks; Francisella tularensis